PERANCANGAN SISTEM LAPORAN KEUANGAN BERBASIS EXCEL DAN PERHITUNGAN PPH FINAL 0,5% UNTUK MENDUKUNG PENGELOLAAN KEUANGAN PADA UMKM SUPER LONTONG - Ivan Ramadhan; Andela Andela; Eri Bestary Al Haitamy (Journal of Applied Accounting And Business, 2026)
UMKM play an important role in the economy; however, many business owners still do not have structured financial records and lack sufficient understanding of tax obligations. This study aims to design a simple financial reporting system using Microsoft Excel in accordance with the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) and to provide a simulation of the 0.5% Final Income Tax based on Government Regulation Number 23 of 2018 at Super Lontong UMKM in Jambi City. This research uses a descriptive qualitative method with data collected through observation, interviews, and documentation. The results indicate that the Excel-based system helps UMKM record transactions more neatly, prepare simple financial statements, and understand their financial condition. In addition, the tax calculation simulation improves business owners’ understanding of tax obligations. Overall, this system is expected to support better financial management and increase tax awareness among UMM.